Energy use changes during a common interval training set at altitude and at sea level
Altitude swimming alters the ability to supply aerobic energy. Consequently, at any given intensity there will be more anaerobic work involved than would be shown at sea level. For example, an EN-1 pace at sea level would represent an EN-2 pace at altitude. This increase in carbohydrate demand means that eating regimens and content have to be altered when training at altitude. Implication: When training at altitude, swimmers have to become almost obsessed with replenishing carbohydrate stores during and between training sessions. If that is not done, then the volume of beneficial training will decrease very rapidly.